2017
DOI: 10.1177/2325967117697950
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Arthroscopic Bankart Repair in Adolescent Athletes Participating in Collision and Contact Sports

Abstract: Background:Literature on arthroscopic stabilization in adolescent patients participating in collision and contact sports is limited, as most studies include adolescents within a larger sample group comprised primarily of adults.Purpose:To review the outcomes of arthroscopic Bankart repair for anterior shoulder instability in an adolescent population participating in collision and contact sports.Study Design:Case series; Level of evidence, 4.Methods:This retrospective review included 39 shoulders in 37 adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 34 publications
2
63
1
1
Order By: Relevance
“…This classification includes in its first category (“contact and collision sports”) sports with a significant variability in terms of the frequency and intensity of the blows and the specific demand imposed on the shoulder. 4 Although this is not the only classification of contact sports, in general most authors report the results encompassing the different types of sport under the name of “contact sports.” 5 , 6 , 7 , 8 , 9 …”
mentioning
confidence: 99%
“…This classification includes in its first category (“contact and collision sports”) sports with a significant variability in terms of the frequency and intensity of the blows and the specific demand imposed on the shoulder. 4 Although this is not the only classification of contact sports, in general most authors report the results encompassing the different types of sport under the name of “contact sports.” 5 , 6 , 7 , 8 , 9 …”
mentioning
confidence: 99%
“…Arthroscopic bankart repair has become gold standard treatment options for patients with traumatic anterior shoulder instability (1,(3)(4)(5)7,16). Several clinical studies have concluded a low rate redislocation and good functional outcomes following arthroscopic anterior stabilization of the shoulder with suture anchors (2,7,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic anterior instability is the most common type of instability in the glenohumeral joint and the most common pathology is antero-inferior labrum lesions (1)(2)(3)(4)(5)(6)(7). Open bankart repair was considered the gold standard procedure in the treatment of traumatic anterior instability; however, arthroscopic repair methods are frequently used recently (2).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to return to athletic competition also depends on the relative risk of injury that is present within each individual sport, with collision and contact athletes historically yielding less favourable outcomes in heterogeneous patient populations. 241418192829 Only a few studies have reported the rates of return to preinjury levels of athletic competition following surgical Bankart repair in the adolescent population. 129283032 There is a further lack of information evaluating the risk of recurrence after open and arthroscopic shoulder stabilisation in the collision and contact adolescent athlete population.…”
Section: Introductionmentioning
confidence: 99%
“…129283032 There is a further lack of information evaluating the risk of recurrence after open and arthroscopic shoulder stabilisation in the collision and contact adolescent athlete population. 28 Additionally, the timetable and surgeon-specific functional criteria required prior to unrestricted return to athletic competition in this age group has been sparsely reported in the literature. 3334 This is important in order to provide general guidelines to aid in determining the appropriate timelines to allow an athlete to unrestricted activity.…”
Section: Introductionmentioning
confidence: 99%